2015
DOI: 10.1111/1346-8138.13068
|View full text |Cite
|
Sign up to set email alerts
|

Psoriasis‐like lesions in a patient with familial Mediterranean fever

Abstract: Familial Mediterranean fever (FMF) is a rare hereditary autoinflammatory disorder that is caused by pyrin gene mutation associated with aberrance of the interleukin (IL)-1b pathway and characterized by recurrent, self-limiting attacks of fever and other inflammatory symptoms. We report a case of FMF with annular erythema and psoriasis-like lesions, the latter of which demonstrated parakeratosis with neutrophil microabscesses and mild inflammatory mononuclear cell infiltration in the upper dermis. Immunofluores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…In this study, there was one HS, one enteropathic arthritis, and three PSA patients. Ashida et al 21 demonstrated Th17 cells in the upper dermis of lesions similar to psoriasis in a patient with FMF. It is estimated that high IL-1 levels in FMF patients may lead to Th17 activation and direct stimulation of keratinocytes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, there was one HS, one enteropathic arthritis, and three PSA patients. Ashida et al 21 demonstrated Th17 cells in the upper dermis of lesions similar to psoriasis in a patient with FMF. It is estimated that high IL-1 levels in FMF patients may lead to Th17 activation and direct stimulation of keratinocytes.…”
Section: Discussionmentioning
confidence: 99%
“…The level Turk J Int Med 2022;4(1): [25][26][27][28][29][30][31][32][33][34][35][36] Familial Mediterranean Fever and Rheumatic Diseases of IL-1 produced by active T lymphocytes is high in psoriasis lesions. 21 FMF and IBD have many similar clinical and biological properties and may accompany FMF. MEFV mutation has been detected in IBD as well, making diagnosis more challenging.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there is an excessive response to normal levels of stress occurring at barrier surfaces or at sites of microdamage, which lead to activations of innate immunity components and in later phases of the adaptive immunity and tissue target damage (20). Furthermore, MEFV mutations have been reported by some case reports to be involved also in some SpA-related disorders, mainly those named “MHC-I-opathies” such as BD, AS, and psoriasis (22, 31, 32).…”
Section: Discussionmentioning
confidence: 99%
“…Ashida et al. have shown the presence of Th17 cells in the upper dermis of psoriasis-like lesions in a patient with FMF ( 11 ). The level of IL-1 which is produced by active T lymphocytes is high in psoriasis lesions ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…There are case reports for the association of psoriasis with FMF ( 11–13 ), and most recently Barut et al. demonstrated an increased frequency of psoriasis in the relatives of pediatric FMF patients in a cohort study ( 14 ).…”
Section: Introductionmentioning
confidence: 99%